Metabolic alterations in urine extracellular vesicles are associated to prostate cancer pathogenesis and progression. Issue 1 (7th May 2018) - Clos‐Garcia, Marc; Loizaga‐Iriarte, Ana; Zuñiga‐Garcia, Patricia; Sánchez‐Mosquera, Pilar; Rosa Cortazar, Ana; González, Esperanza; Torrano, Verónica; Alonso, Cristina; Pérez‐Cormenzana, Miriam; Ugalde‐Olano, Aitziber; Lacasa‐Viscasillas, Isabel; Castro, Azucena; et al.
ABSTRACT: Urine contains extracellular vesicles (EVs) that concentrate molecules and protect them from degradation. Thus, isolation and characterisation of urinary EVs could increase the efficiency of biomarker discovery. We have previously identified proteins and RNAs with differential abundance in urinary EVs from prostate cancer (PCa) patients compared to benign prostate hyperplasia (BPH). Here, we focused on the analysis of the metabolites contained in urinary EVs collected from patients with PCa and BPH. Targeted metabolomics analysis of EVs was performed by ultra‐high‐performance liquid chromatography–mass spectrometry. The correlation between metabolites and clinical parameters was studied, and metabolites with differential abundance in PCa urinary EVs were detected and mapped into cellular pathways. We detected 248 metabolites belonging to different chemical families including amino acids and various lipid species. Among these metabolites, 76 exhibited significant differential abundance between PCa and BPH. Interestingly, urine EVs recapitulated many of the metabolic alterations reported in PCa, including phosphathidylcholines, acyl carnitines, citrate and kynurenine. Importantly, we found elevated levels of the steroid hormone, 3beta‐hydroxyandros‐5‐en‐17‐one‐3‐sulphate (dehydroepiandrosterone sulphate) in PCa urinary EVs, in line with the potential elevation of androgen synthesis in this type of cancer. This work supports urinary EVs as a non‐invasive source to infer metabolic changes in PCa.